Minimizing lithium deactivation during high-rate electroplating via sub-ambient thermal gradient control. (December 2020) - Atkinson, R.W.; Kingston, T.A.; Klein, E.J.; NewRingeisen, A.; Carter, R.; Love, C.T.
Abstract: The reversibility of Li electrodeposits must be significantly improved for Li metal anodes to be realized for next-generation, high energy density batteries. The most commonly tested thermal condition in the Li metal battery literature is isothermal ~20 °C (ambient). Elevating the cell temperature (40 °C) improves Li metal stability by suppressing dendritic growth at the expense of augmenting solid electrolyte interphase growth. However, at the high current density and areal capacity tested in this work (10 mA cm −2, 3.0 mA h cm −2 ), dendritic growth is inevitable and Li metal electrodes succumb to extensive degradation due to Li deactivation. To overcome these shortcomings of isothermal cycling, we expand on our concept of an interelectrode thermal gradient, which enhances Li surface diffusion to homogenize Li electroplating. With mean temperatures near ambient, a thermal gradient (ΔTwarm : 22.6 °C negative electrode, 21.4 °C positive electrode) delays failure compared with isothermal control (20 °C). The greatest benefit of the thermal gradient is unlocked at sub-ambient electrode temperatures. By applying the thermal gradient at low temperatures (ΔTcold : 3.7 °C negative electrode, 2.0 °C positive electrode), SEI growth stifles, dendrite propagation suppresses, and Li deactivation minimizes, stabilizing high-rate Li electroplating and stripping. After 100 cycles, ΔTcold reduces voltage hysteresis and electrode resistance by 51% and 77%, respectively, compared with the most promising isothermal condition (40 °C). Operando optical visualization confirms more reversible and dense Li electrodeposition via sub-ambient thermal gradient control with higher first-cycle Coulombic efficiency in an anode-free configuration. By contrast, isothermal 20 °C control exacerbates porous and dendritic Li electrodeposition with low reversibility. Graphical abstract: Image 1 Highlights: With isothermal control, higher cell temperature (40 °C) improves Li electroplating stability at very high current density. Significant electrolyte and Li electrode degradation are observed after repeated electroplating and stripping at 40 °C. Electrochemical signatures of dendritic Li electroplating are observed for all thermal controls at 10 mA/cm 2 . Sub-ambient thermal gradient control minimizes Li electrode and electrolyte degradation. Operando optical microscopy confirms denser Li electroplating via sub-ambient thermal gradient.